2019
DOI: 10.1002/pssa.201900589
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Hematite Decorated with Gold Nanoparticles for Functionalization and Biocompatibility

Abstract: Iron oxides have attracted the attention of researchers due to their abundance, low cost, low toxicity, and versatility of applications. According to the composition and crystalline structure, iron oxides may have characteristics of semiconductors and magnetic materials, such as hematite (α‐Fe2O3) and magnetite (Fe3O4), respectively. The property of biocompatibility of hematite is essential to be applied in the construction of micro‐/nanorobots (MNRs). Herein, the decoration of hierarchically structured core/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Combining the merit and demerit of the α-Fe , but its experimental period was length. Menezes et al [22] prepared Fe 2 O 3 /Fe 3 O 4 microtubes via the thermal oxidation process of a high-purity metallic iron microwire. However, the temperature of the experimental process was too high to apply widely, and Fe 2 O 3 /Fe 3 O 4 microtubes had a larger diameter and uncontrollable magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the merit and demerit of the α-Fe , but its experimental period was length. Menezes et al [22] prepared Fe 2 O 3 /Fe 3 O 4 microtubes via the thermal oxidation process of a high-purity metallic iron microwire. However, the temperature of the experimental process was too high to apply widely, and Fe 2 O 3 /Fe 3 O 4 microtubes had a larger diameter and uncontrollable magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been dedicated to combine different semiconductors into a single heterostructured system in order to achieve new improved properties. , Among the possibilities of using heterostructure hollow materials based on the Fe 2 O 3 /Fe 3 O 4 microarchitecture, recent reports have shown that the microtube modification with plasmonic nanoparticles increases biocompatibility, electronic transport, and light-assisted charge transfer, which opens up opportunities for applications in micro and bioelectronics. , …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the spatial structure of molecules and the oxidation state of iron, there are three most common forms of IONPs structurally corresponding to iron oxide minerals: magnetite (FeO*Fe 3 O 4 ), maghemite (γ-Fe 2 O 3 ), and hematite (α-Fe 2 O 3 ) [5]. While α-Fe 2 O 3 nanostructures are applied in designing micro/nanorobots [6,7], FeO*Fe 3 O 4 and γ-Fe 2 O 3 are widely used in diagnostics and therapy. In practice, these are employed in the treatment of iron deficiency anemia [8], as a contrast agent for magnetic resonance imaging (MRI) [9,10], and in the development of various antitumor strategies: magnetic hyperthermia [11,12], targeted delivery, and tumor sensitization [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%